Microtubules Regulate Hypoxia-inducible Factor-1α Protein Trafficking and Activity: IMPLICATIONS FOR TAXANE THERAPY - Carbonaro, Marisa (American Society for Biochemistry and Molecular Biology, 2012)
Disruption of the microtubule cytoskeleton impairs tumor angiogenesis by inhibiting the hypoxia-inducible factor (HIF-1α) pathway. However, the signaling cascade linking microtubule disruption to HIF-1α inactivation has not been elucidated. Here, we show that microtubule-targeting drug (MTD) treatment impaired HIF-1α protein nuclear translocation, which significantly down-regulated HIF transcriptional activity. We provide strong evidence that HIF-1α protein associates with polymerized microtubules and traffics to the nucleus, with the aid of the dynein motor protein. Together, these data suggest that microtubules are critically involved in the nuclear trafficking and transcriptional activity of HIF-1α. We also show that the connection between the microtubule cytoskeleton and HIF-1α regulation is lost in renal cell carcinoma (RCC), where HIF-1α is overexpressed because of mutations in the von Hippel Lindau (VHL) tumor suppressor protein. Specifically, we show that MTD treatment of RCC cells did not impair HIF-1α nuclear accumulation or transcriptional activity, and had no effect on the polysome association profile of HIF-1α. Interestingly, we found that HIF-1α protein did not bind microtubules in RCC. Moreover, restoration of VHL function failed to restore the ability of MTDs to inhibit HIF-1α, suggesting that VHL does not contribute to this phenotype. Together, these results suggest that HIF-1α regulation is microtubule-independent, and likely contributes to the chemoresistant nature of RCCs. Further understanding of the microtubule-dependent HIF-1α regulation, and lack thereof in RCC, is essential given the importance of HIF-1α in tumor biology, and the widespread use of MTDs in clinical oncology.